Human Trafficking in Malaysia: Bureaucratic Challenges in Policy Implementation - Wan Ismail, Wan Nur Ibtisam; Raja Ariffin, Raja Noriza; Cheong, Kee Cheok (SAGE Publications, 2017)
Recent studies have suggested that migrants are highly vulnerable to being trafficked. Malaysia, with its large number of migrants is vulnerable and is struggling to implement its Anti-Trafficking in Persons and Anti-Smuggling of Migrants Act 2007. There is also little information on implementation experience so far. Through in-depth interviews with government bureaucrats and other stakeholders, this study seeks to gain some insight into Malaysia’s policy implementation experience. It finds inadequate coordination, limited resources, poor information flow, enforcement approach, hierarchical control structure, and need for change as the major factors constraining effective policy implementation.